2015
DOI: 10.1038/tp.2015.32
|View full text |Cite
|
Sign up to set email alerts
|

Maternal depression is associated with DNA methylation changes in cord blood T lymphocytes and adult hippocampi

Abstract: Depression affects 10–15% of pregnant women and has been associated with preterm delivery and later developmental, behavioural and learning disabilities. We tested the hypothesis that maternal depression is associated with DNA methylation alterations in maternal T lymphocytes, neonatal cord blood T lymphocytes and adult offspring hippocampi. Genome-wide DNA methylation of CD3+ T lymphocytes isolated from 38 antepartum maternal and 44 neonatal cord blood samples were analyzed using Illumina Methylation 450 K mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 48 publications
3
90
0
Order By: Relevance
“…NR3C1 is not the only locus where DNA methylation is modified by maternal stress. Other methylation changes in offspring exposed to maternal depression were detectable in the immune system at birth and persisted until adulthood in the hippocampus, a known regulator of HPA activity (54).…”
Section: Discussionmentioning
confidence: 99%
“…NR3C1 is not the only locus where DNA methylation is modified by maternal stress. Other methylation changes in offspring exposed to maternal depression were detectable in the immune system at birth and persisted until adulthood in the hippocampus, a known regulator of HPA activity (54).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study by Rodney et al [48] found that infants whose mothers had experienced severe war stress during pregnancy had 212 differentially methylated CpG regions in cord blood, compared to non-exposed control infants. Nemoda et al [49] studied T lymphocyte methylation patterns in the neonatal cord blood of both infants whose mothers experienced prenatal depression and infants whose mothers did not experience prenatal depression. They found that infants in the prenatal depression group had 2520 differentially methylated CpG sites as compared to controls, and that 75.5% of these sites were hypomethylated.…”
Section: Proposed Biological Mechanisms: Epigeneticsmentioning
confidence: 99%
“…A previous study on genome-wide DNA methylation profiling identified that DNA methylation levels were lower in patients with major depressive disorder compared with controls and that the majority of the methylated sites (85.7%) were located on the promoter CpG islands (34). Additionally, a previous study suggested that maternal depression is associated with DNA methylation changes in cord blood T lymphocytes and adult hippocampi (35). In the present study, a positive correlation between CpG5 methylation and depression-dejection was detected in heroin addicts, indicating that the DRD4 CpG5 methylation level may contribute to the onset of depression in heroin addicts.…”
Section: P-value Subgroups ------------------------------------------mentioning
confidence: 97%